MUI and Its Fatwa: The Articulation of Modern Authority in a Religious Democracy of Indonesia - Ach. Fatayillah Mursyidi (IAIN Madura, 2020)
Indonesian Council of Ulama (MUI) has been politically the most influential religious organization in Indonesia since its initial establishment in 1975. By issuing a series of fatwa, this organization has religiously encouraged Indonesian Muslim to behave and take any decision within their life in accordance with Islamic stipulation based on the institutional interpretation. Though known and widely accepted as legal opinion on religious issues, one of among the most controversial fatwa recently issued by the MUI was, in fact, related to the civil participation in the last but most contentious general election. The fatwa theologically declared a religious status of being abstain (golput) in the election; that is religiously disallowed (haram). By referring to the statistic data of golput, it is shockingly evidenced that the fatwa has somehow influenced Muslim voters to use their civil rights properly in this presidential election.Considering those startling facts, this paper aims to see how religious precepts are efficaciously employed by MUI to endorse the democratic system of Indonesia. Through broader analytical observation on the dynamic of MUI’s political movement in the light of Menchikian periodization of MUI’s authority, I argued that modern strategies, such as those including mass mobilization, lobbying, and coercive power, are currently applied to claim their authority amid Indonesian society.